Cigarette smoke restricts the ability of mesenchymal cells to support lung epithelial organoid formation - Khedoe, P. P. S. J.; van Schadewijk, W. A. A. M.; Schwiening, M.; Ng-Blichfeldt, J. P.; Marciniak, S. J.; Stolk, J.; Gosens, R.; Hiemstra, P. S. (Frontiers in Cell and Developmental Biology, 2023)
Adequate lung epithelial repair relies on supportive interactions within the epithelial niche, including interactions with WNT-responsive fibroblasts. In fibroblasts from patients with chronic obstructive pulmonary disease (COPD) or upon in vitro cigarette smoke exposure, Wnt/β-catenin signalling is distorted, which may affect interactions between epithelial cells and fibroblasts resulting in inadequate lung repair. We hypothesized that cigarette smoke (CS), the main risk factor for COPD, interferes with Wnt/β-catenin signalling in fibroblasts through induction of cellular stress responses, including oxidative- and endoplasmic reticulum (ER) stress, and thereby alters epithelial repair support potential. Therefore, we assessed the effect of CS-exposure and the ER stress inducer Thapsigargin (Tg) on Wnt/β-catenin signalling activation in MRC-5 fibroblasts, and on their ability to support lung epithelial organoid formation. Exposure of MRC-5 cells for 15 min with 5 AU/mL CS extract (CSE), and subsequent 6 h incubation induced oxidative stress (HMOX1). Whereas stimulation with 100 nM Tg increased markers of both the integrated stress response (ISR - GADD34/PPP1R15A, CHOP) and the unfolded protein response (UPR - XBP1spl, GADD34/PPP1R15A, CHOP and HSPA5/BIP), CSE only induced GADD34/PPP1R15A expression. Strikingly, although treatment of MRC-5 cells with the Wnt activator CHIR99021 upregulated the Wnt/β-catenin target gene AXIN2, this response was diminished upon CSE or Tg pre-exposure, which was confirmed using a Wnt-reporter. Furthermore, pre-exposure of MRC-5 cells to CSE or Tg, restricted their ability to support organoid formation upon co-culture with murine pulmonary EpCam+ cells in Matrigel at day 14. This restriction was alleviated by pre-treatment with CHIR99021. We conclude that exposure of MRC-5 cells to CSE increases oxidative stress, GADD34/PPP1R15A expression and impairs their ability to support organoid formation. This inhibitory effect may be restored by activating the Wnt/β-catenin signalling pathway.